Growth Through Suffering. On Writing the Realistic Novella A Nightmarish Life - Þuríður Sóley Sigurðardóttir 1990- (2019)
The following BA-thesis consists of the novella A Nightmarish Life (16,176 words) and an exposition (4,890 words). The objective of this creative writing project is to set up a realistic plot in contemporary Iceland, enabling the reader to observe true to life characters as they drive the plot onwards, and are forced to make difficult ethical choices as the events of the story unfold. By applying three different point of views—with each view centring around a specific character—the story has three contrasting tones for the reader to experience. At the start of the journey the reader watches through the eyes of Grímur, who is narrating the worst day of his life from the first-person point of view; then from the second-person point of view the reader experiences the pain of Sölva as she makes unredeemable choices in a response to her younger sister’s death; and from the third-person point of view the reader follows the investigative journalist Alex as he is forced into the plot, giving the reader a familiar sense of the detective novel—with a twist at the end. When the story begins Sölva commits a horrible crime against Grímur, whom she blames for her sister’s death. The story then revolves around the developments that unfold from that fateful event; and Sölva’s reasons for her hatred towards Grímur. As a realistic revenge story, it centres around modern sexual crimes, social revolutions, and the effects grief can have on an individual. The exposition then explains in detail: the meaning behind the plot; the work that went into writing the story; its narrative elements, and the creative progress.